Focus position and depth of two-dimensional patterning by Talbot effect lithography - Sato, Takashi (Microelectronic Engineering, 2014)
The Talbot effect is a self-imaging phenomenon enabling lens-less imaging. The interval of the focus position is called the Talbot distance. To maintain pattern fidelity, the accurate focus position of the self-imaging needs to be known. The depth of focus based on Rayleigh's criterion is analytically a quarter of the Talbot distance. In a hexagonal array of a fine pitch, the Talbot distance derived from 2nd-order approximation is inaccurate. The analytically accurate expression of the Talbot distance for hexagonal arrays is shown in imaging of low-order diffraction rays.